Harnessing biocontrol potential of Trichoderma harzianum for control of Meloidogyne incognita in tomato - DEEPTI MALVIYA, RAJAN CHAURASIA, MOHD. IMRAN, JAI P. RAI and ARUN K. SHARMA, UDAI B. SINGH*, SHAILENDRA SINGH (Indian Phytopathology, 2017)
The aim of the study was to evaluate the biocontrol potential of Trichoderma harzianum against Meloidogyne incognita and decipher mechanisms of induced systemic resistance and disease suppression in tomato grown in net house conditions. The fungal biocontrol agent T. harzianum UBSTH-501 was evaluated against M. incognita on dual plate under in vitro conditions and in planta under nethouse conditions. The results of in vitro parasitism on dual plates showed that T. harzianum causing infection on the eggs and juveniles of root-knot nematode, whereas, in planta assay showed that plants treated with talc based bioformulation T. harzianum UBSTH-501 exhibited manifold increase in the accumulation of total chlorophyll and enzymes, viz. chitinase, phenylalanine ammonia lyase (PAL) and peroxidase which is known to confer systemic resistance in tomato against M. incognita resulting into decreased nematode population and disease severity. Results revealed that T. harzianum UBSTH-501modulated phenylpropanoid pathways led to enhanced accumulation of defence related mediator molecules and enzymes in tomato resulted in disease suppression to a significant extents.